Experimental Investigation of Concrete Utilizing Rice Husk, Iron Slag and Silica Fumes to Enhance its Properties A Review - Savita Choudhari; Sulekha Patel; Ravindra Gautam (International Journal of Scientific Research in Civil Engineering, 2022)
As per the statistics India has used around 379 million metric tons of concrete in the financial year 2022 proving to be the most widely used construction material due to its versatility and holds the property of being customized as per the environmental requirement. Without the excessive usage of concrete, human development is impossible in today’s reality. Concrete’s most significant component is cement. Unfortunately, cement production emits a substantial amount of greenhouse gases and poses a significant threat to the environment. As a result, lowering the reliance on cement for concrete strength is unavoidable for the long-term growth of human life. This is the primary reason for seeking an appropriate cement substitute in order to get high-strength concrete at a reasonable cost. In addition, modern projects necessitate extremely high concrete strength, which can only be achieved by properly combining admixtures into the concrete. In India, industrial waste materials such as silica fume, rice husk ash, and iron slag are readily available. Their disposal has become pricey as a result of recent implemented norms and restrictions. As a result, it is vital to identify a viable use for these waste products. Because of their high siliceous content and pozzolanic qualities, these materials can be utilised to substitute cement in concrete mixes and as admixtures to achieve high strength. The two most significant parameters that determine the performance of concrete in any field application are flexural and compressive strengths. It’s crucial to figure out how these admixtures affect concrete’s flexural and compressive strength. In this research we are presenting review of literature related to concrete technology.